MANAGEMENT OF EDUCATIONAL ASSESSMENT - Badrudin, Badrudin; Badrudin, M. Badar; Maulida, Julia Nur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This journal presents a qualitative descriptive case study investigating the management of educational assessment at MAS Darussalam. Specific objectives include examining the assessment policies, exploring the challenges faced by educators and administrators, and proposing recommendations for improvement. The research adopts a qualitative approach, emphasizing in-depth exploration and understanding of the educational assessment management at MAS Darussalam. Data is collected through methods semi-structured interviews, document analysis, and participant observations. This approach allows for a nuanced exploration of the experiences, perspectives, and practices related to educational assessment. Data analysis techniques are data reduction, data presentation and drawing conclusions. Meanwhile, the data validity test used triangulation technique. The research findings offer insights into the current state of educational assessment management at MAS Darussalam. This includes an overview of existing assessment policies, identification of challenges faced by educators and administrators, and recommendations for enhancing the effectiveness of educational assessment practices. The case study contributes to the broader discourse on educational assessment management, offering valuable lessons and considerations for similar educational institutions.